Educação À Distância (Ead) E Cibercultura: Para Além Da Reprodução Na Educação - Pacheco, Frederico Reis [UNIFESP] (2017)
The aim of this study is to evaluate new forms of teaching mediated by technology (in particular Distance Learning for higher education), in terms of its potentialities and limitations, in a reflexive philosophical way. The hypothesis raised in this study is divided into two bases: (1) that technology can be understood as an opportunity for education in new territories, without part of the limits existing in conventional education, expanding possibilities; but (2) technology-mediated education has been used in Brazil to reproduce pre-existent addictions in the educational system, such as the reproduction of the current educational model, its limits, habits, and disciplinary or control engines. The method selected for this work was the exploratory bibliographical research and critical literature review on the theme of Distance Learning (e-learning), triggering a classical theoretical reference of philosophy and education to ensure the correct evaluation of the technologies and their use in the teaching-learning process. The leading thread of this thinking is Pierre Levy's theory of cyberculture, provoking his dialogue with other authors on each topic addressed. Thus, the relevance of this work is on deepening of a critical analysis on the use of technology, with a focus as learning tool, without technological dazzle. The limit of this analysis is the use of technology for distance learning in the upper level of the Brazilian territory. This vision is expected to be relevant to contribute to the construction of micro-initiatives that will enable a more inclusive education focused on student's experience.